HIF-1α and mTOR: possible novel strategies of targeted therapies in p16-positive and -negative HNSCC - Kramer, Benedikt; Polit, Max; Rotter, Nicole; Aderhold, Marc Christoph (Cancer genomics & proteomics, 2018)
Background/Aim: Targeted therapy in head and neck squamous cell carcinoma (HNSCC) is limited. HIF-1α and mTOR are involved in the formation of local tumor progression and distant metastasis. The present study analyzed the influence of well-established tyrosine kinase inhibitors nilotinib, dasatinib, erlotinib and gefitinib on the expression of HIF-1α and mTOR in p16-positive and -negative squamous cancer cells (SCC) in vitro in order to develop novel strategies in the treatment of HNSCC. Materials and Methods: Expression of HIF-1α and mTOR was analyzed by using Sandwich-ELISA in p16-negative and p16-positive SCC after treatment with nilotinib, dasatinib, erlotinib and gefitinib (20 μmol/l, 24-96 h of incubation). Results: All substances significantly reduced mTOR expression in both, p16-negative and p16-positive SCC (p<0.05). HIF-1α expression was significantly reduced by all tested substances in p16-negative SCC. However, a statistically significant increase of HIF-1α was observed in p16-positive SCC. Conclusion: This is the first study to investigate the alteration of expression levels of HIF-1α and mTOR under selective tyrosine kinase inhibition in both p16-positive and -negative SCC. Our findings provide novel insights for a better understanding of HIF-1α and mTOR in the tumor biology of HNSCC and their interaction with selective small-molecule inhibitors.